Comparison of Different Protein Concentration Strategies by Two-Dimensional Gel Electrophoresis of Human Serum Proteomics - Liu, Wentao; Yang, Ling; Liu, Bingya; Cai, Qu; Zhang, Yi; Chen, Xuehua; Yang, Qiumeng; Zhu, Zhenggang (Asian Journal of Chemistry, 2010)
In the research of serum proteomics, an appropriate sample preparation is essential for obtaining good results in two dimensional electrophoresis (2-DE). The concentration steps are necessary to sample preparation and several other processes. Our goal is to find the most efficient method that minimally impacted on serum proteins for a serum proteomics. We compared three strategies of concentration including ReadyPrep 2-D cleanup kit, freeze-drying and ultrafiltration using crude serum samples and high abundant proteins depleted serum samples. By comparing the different characteristics of the operation process, the recovery effect and the compatibility with 2-DE, it is found that the freeze-drying and ultrafiltration performed an efficient sample concentration of serum proteins. And all of these three concentration strategies delivered a satisfied compatibility with 2-DE technique of serum proteomics. Less manual operations involved in concentration procedures was expected to provide a more reliable result of serum proteomics.